2019
DOI: 10.1038/s41598-019-48053-z
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial RhoA GTPase is essential for in vitro endothelial functions but dispensable for physiological in vivo angiogenesis

Abstract: Imbalanced angiogenesis is a characteristic of several diseases. Rho GTPases regulate multiple cellular processes, such as cytoskeletal rearrangement, cell movement, microtubule dynamics, signal transduction and gene expression. Among the Rho GTPases, RhoA, Rac1 and Cdc42 are best characterized. The role of endothelial Rac1 and Cdc42 in embryonic development and retinal angiogenesis has been studied, however the role of endothelial RhoA is yet to be explored. Here, we aimed to identify the role of endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 78 publications
(130 reference statements)
1
36
0
Order By: Relevance
“…Cell migration assay was performed using a 48-well Boyden chamber, as described previously [16,34]. Briefly, the upper chamber and lower chamber were separated by an 8-µm pore size polyvinyl pyrrolidone-free polycarbonate membrane (NeuroProbe) coated with collagen.…”
Section: Cell Migration Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Cell migration assay was performed using a 48-well Boyden chamber, as described previously [16,34]. Briefly, the upper chamber and lower chamber were separated by an 8-µm pore size polyvinyl pyrrolidone-free polycarbonate membrane (NeuroProbe) coated with collagen.…”
Section: Cell Migration Assaymentioning
confidence: 99%
“…Tube formation assay was performed with serum-starved HUVECs using growth factor-reduced matrigel, as previously described [16,32,35]. Wells of a 96-well culture plate were carefully coated to avoid bubble formation, with 40 µL/well RGF-Basement membrane extract.…”
Section: Tube Formation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…In NEK9 immunoprecipitates, it was shown that NEK9 interacts with both Rho GTPase‐activating protein 11A, as well as myosin phosphatase Rho‐interacting protein. Both proteins are regulators of endothelial permeability . It was suggested that NEK9 forms two separate signaling modules: The first one is composed of NEK6 and Mklp2, and the second one is consisted of NEK7 and the Kinesin‐like protein KIF20A.…”
mentioning
confidence: 99%
“…Both proteins are regulators of endothelial permeability. 25 It was suggested that NEK9 forms two separate signaling modules: The first one is composed of NEK6 and Mklp2, and the second one is consisted of NEK7 and the Kinesin-like protein KIF20A. Indeed, NEK9 activates NEK6 and NEK7 by releasing autoinhibitory conformations through direct binding, as well as by phosphorylating the corresponding activation sites.…”
mentioning
confidence: 99%